Modelling and simulation of faults in synchronous generators for robust numerical protection - Sinha A.; Vishwakarma D.N.; Srivastava R.K. (My University, 2025)
When an internal fault occurs in a synchronous generator, the symmetry between the parallel paths of the winding is broken and different currents flow in them, due to unsymmetrical magnetic linkage between the stator windings. The aim of this paper is to present a simulation model to investigate the effect of internal fault on the parallel path currents of a large synchronous generator using direct phase quantities. This model is based on a modified winding function approach where the machine inductances are calculated directly from the machine winding distribution using machine electrical parameters instead of the geometrical ones. The simulation results for different cases of internal faults in salient-pole and non-salient-pole synchronous machines have been obtained. Salient-pole synchronous generator has wave winding distribution while the non-salient-pole generator has lap winding arrangement. Due to different stator winding arrangements, the two machines have been simulated individually. By using the simulated fault data, a suitable numerical protection scheme for synchronous generators can be developed. Copyright © 2012 Inderscience Enterprises Ltd.